Optimization of a clofarabine‐based drug combination regimen for the preclinical evaluation of pediatric acute lymphoblastic leukemia. Issue 4 (25th December 2019) - Xie, Jinhan; Span, Miriam; van Maarseveen, Erik; Langenhorst, Jurgen; Boddy, Alan V.; Sia, Keith C.S.; Sutton, Rosemary; Venn, Nicola; Punt, Arjen M.; Tyrrell, Vanessa; Haber, Michelle; Trahair, Toby; et al.
Abstract: Background: The aim of this study was to improve the predictive power of patient‐derived xenografts (PDXs, also known as mouse avatars) to more accurately reflect outcomes of clofarabine‐based treatment in pediatric acute lymphoblastic leukemia (ALL) patients. Procedure: Pharmacokinetic (PK) studies were conducted using clofarabine at 3.5 to 15 mg/kg in mice. PDXs were established from relapsed/refractory ALL patients who exhibited good or poor responses to clofarabine. PDX engraftment and response to clofarabine (either as a single agent or in combinations) were assessed based on stringent objective response measures modeled after the clinical setting. Results: In naïve immune‐deficient NSG mice, we determined that a clofarabine dose of 3.5 mg/kg resulted in systemic exposures equivalent to those achieved in pediatric ALL patients treated with clofarabine‐based regimens. This dose was markedly lower than the doses of clofarabine used in previously reported preclinical studies (typically 30‐60 mg/kg) and, when scheduled consistent with the clinical regimen (daily × 5), resulted in 34‐fold lower clofarabine exposures. Using a well‐tolerated clofarabine/etoposide/cyclophosphamide combination regimen, we then found that the responses of PDXs better reflected the clinical responses of the patients from whom the PDXs were derived. Conclusions: This study has identified an in vivo clofarabine treatment regimen that reflects the clinical responses of relapsed/refractory pediatric ALL patients. This regimen could be used prospectively to identify patients who might benefit from clofarabine‐based treatment. Our findings are an important step toward individualizing prospective patient selection for the use of clofarabine in relapsed/refractory pediatric ALL patients and highlight the need for detailed PK evaluation in murine PDX models.